ANALISIS PENANGANAN KONSENTRASI HIDROGEN SULFIDA DALAM MINYAK BUMI LAPANGAN TIAKA KABUPATEN MOROWALI UTARA PROVINSI SULAWESI TENGAH (Jurnal Geomine, 2016)
Hydrogen Sulfide (H2S) is a material that is extremely poisonous, colorless, in low concentrations smells like rotten eggs and is heavier than air also. The purpose of this research is to reduce the concentration of H2S gas from its source to reach a concentration of 10 ppm. The research method is done by Process Acid Gas Removal or the removal of acid gas (hydrogen sulfide) with chemical injection method H2S Scavenger, including data required monitoring data and the H2S concentration of oil production data. This research was conducted with the system monitoring the concentration of H2S gas per day on the manifold, storage tank (T500), and at the FSO or tanker petroleum final collection point. After optimization with changes in dose injection of chemicals as much as 5,6,7,8 and 9 gallons per day of injection of chemicals found as many as nine gallons per day the most appropriate to reduce the concentration of H2S gas from its source to reach a concentration of 10 ppm when the oil has processed into the final holding tank.